(untitled) (Journal of Small Business Strategy (archive only), 1999)
There is no question that timely and accurate information is as valuable to small business decision makers as it is to decision makers in large organizations. Interestingly though, evidence exists that small businesses make little use of (Oumlil, 1989; Hall, Anglin, and Elliott, 1997; McDaniel and Parasuraman, 1986), and place limited value on (Brush, 1992; Callahan and Cassar, 1995), marketing research – the very discipline capable of providing this valuable information.